Rate of reversal of hypercalcaemia and hypercalciuria induced by vitamin D and its 1alpha-hydroxylated derivatives. Issue 6053 (8th January 1977) - Kanis, J A; Russell, R G
Abstract : The rate of reversal of hypercalcaemia or hypercalciuria induced by calciferol, dihydrotachysterol, 1-alpha-hydroxycholecalciferol (1-alpha-OHD3), or 1-alpha, 25-dihydroxycholecalciferol (1-alpha, 25-(OH)2D3) was measured in three normal subjects, two patients with osteoporosis, and 14 patients with disorders resistant to vitamin D. The half time for reversal after stopping 1-alpha, 25 (OH)2D3 was less than that after stopping 1-alpha-OHD3, calciferol, or dihydrotachysterol. The differences observed were independent of the dose given or length of treatment. When 1-alpha-OHD3 or 1-alpha-25-(OH)2D3 was stopped patients with vitamin D resistant states (hypoparathyroidism, renal tubular hypophosphataemia, or chronic renal failure) showed less rapid reversal of hypercalcaemia and hypercalciuria than did normal subjects. These studies show one potential advantage of 1-alpha-25-(OH)2D3 over vitamin D, and possibly over 1-alpha-OHD3, in the management of vitamin D resistant states.